Depression, Anxiety, Stress and Its Association with Coping Strategies among Malaysian University Students - Abdul Halim, Bushra; Fuzi, Siti Fairus; Jama, Siti Ramizah; Zainudin, Siti Nursyahira; Jusoh, Nordianah; Zahidi, Nurul Emyza; Wan Hassan, Wan Hartini (Information Management and Business Review, 2024)
Malaysia is one of the countries transitioning from the pandemic phase to an endemic phase of Covid-19. The spread of Covid-19 had a significant impact on university students, affecting their mental health just as it did for many others. This study investigates depression, anxiety, and stress symptom levels among Malaysian university students and the coping strategies used to prevent or reduce these psychological distress symptoms. A web-based questionnaire was developed using Google Forms to collect data from students who were selected non-randomly from three public universities and one from a private university in Malaysia. Patient Health Questionnaire-9 (PHQ-9), Generalized Anxiety Disorder-7 (GAD-7), and Perceived Stress Scales-10 (PSS-10) were used for measuring depression, anxiety, and stress respectively. The coping strategies were measured using five strategies: seeking social support for emotional reasons, seeking social support for instrumental reasons, acceptance, mental disengagement, and humanitarian. The study findings indicated that 60.7% had depression symptoms, 30.4% had anxiety symptoms, and 86.3% had stress symptoms at moderate-to-severe levels. Acceptance was the most preferred coping strategy among the students while seeking social support for instrumental reasons was the least preferred coping strategy. Students with severe depression levels used mental disengagement coping strategies more than those with mild symptoms. Mental disengagement coping strategy was associated with severe anxiety symptoms compared to mild and minimal symptoms. Seeking social support for emotional reasons was also associated with moderate anxiety symptoms compared to mild anxiety symptoms.